Contradictory roles of lipid metabolism in immune response within the tumor microenvironment - Yu, Weina; Lei, Qingyang; Yang, Li; Qin, Guohui; Liu, Shasha; Wang, Dan; Ping, Yu; Zhang, Yi (Journal of hematology and oncology, 2021)
Complex interactions between the immune system and tumor cells exist throughout the initiation and development of cancer. Although the immune system eliminates malignantly transformed cells in the early stage, surviving tumor cells evade host immune defense through various methods and even reprogram the anti-tumor immune response to a pro-tumor phenotype to obtain unlimited growth and metastasis. The high proliferation rate of tumor cells increases the demand for local nutrients and oxygen. Poorly organized vessels can barely satisfy this requirement, which results in an acidic, hypoxic, and glucose-deficient tumor microenvironment. As a result, lipids in the tumor microenvironment are activated and utilized as a primary source of energy and critical regulators in both tumor cells and related immune cells. However, the exact role of lipid metabolism reprogramming in tumor immune response remains unclear. A comprehensive understanding of lipid metabolism dysfunction in the tumor microenvironment and its dual effects on the immune response is critical for mapping the detailed landscape of tumor immunology and developing specific treatments for cancer patients. In this review, we have focused on the dysregulation of lipid metabolism in the tumor microenvironment and have discussed its contradictory roles in the tumor immune response. In addition, we have summarized the current therapeutic strategies targeting lipid metabolism in tumor immunotherapy. This review provides a comprehensive summary of lipid metabolism in the tumor immune response.